BC Reads Adult Literacy Fundamental English - Ivits, Shantel (Open textbook library., 2015)
This course pack is designed to meet the learning outcomes for Adult Literacy Fundamental English Level 6 (roughly equivalent to grades 7.5 to 9 in the K-12 system). Every chapter includes a level-appropriate, high-interest reading of between 500 and 1,000 words. The readings are freely available in a separate reader with convenient links to the readings in each chapter of this course pack. Font size and line spacing can be adjusted in the online view, and have been enhanced for the print and PDF versions for easier reading. This course pack has been reviewed by subject experts from colleges and universities.